Tindak Tutur Ekspresif Deddy Corbuzier dalam Video Podcast di Youtube - Febyuharnedi; Ermanto Ermanto (Persona: Kajian Bahasa dan Sastra, 2023)
The purpose of this research is to (1) describe the forms of expressive speech acts used by Deddy Corbuzier in video podcasts on Youtube. (2) describe the form of speech strategy used by Deddy Corbuzier in video podcasts on Youtube. This type of research is qualitative research using descriptive methods. The research data is in the form of utterances that contain expressive speech acts in video podcasts on Youtube used by Deddy Corbuzier, while the data source for this research is Deddy Corbuzier's video podcast which presents government officials as resource persons. Based on the results of the study, it was concluded that Deddy Corbuzier dominantly used expressive speech acts to criticize, because the video podcasts studied were video podcasts that presented government officials as resource persons, indicating that many criticisms were conveyed by Deddy Corbuzier to government officials as citizens. Meanwhile, the strategy of speaking frankly without further ado is dominant because the strategy of speaking frankly without further ado is a speaking strategy in which the speech is told as it is without preamble in its delivery.